Effectiveness of Cornfish Nuggets on Nutrient Intake, Mid-Upper Arm Circumference (MUAC), and Body Weight among Pregnant Women with Chronic Energy Deficiency (CED) - Adelia Pratiwi; Ahmad Sadiq; Mardiana; Nurul Salasa Nilawati; Eliza (JURNAL RISET GIZI, 2026)
Background: Chronic Energy Deficiency (CED) among pregnant women remains a nutritional problem in Indonesia, with a prevalence of 16.9% in 2023. In South Sumatra Province, the prevalence of CED among pregnant women was reported at 4.2% in 2022. CED increases the risk of various maternal and fetal complications, highlighting the need for effective nutritional interventions. Cornfish nuggets, made from snakehead fish and corn, are a local food-based supplementary product rich in energy and protein that may improve nutrient intake, mid-upper arm circumference (MUAC), and body weight among pregnant women with CED. Objective: This study aimed to analyze the effectiveness of Cornfish nugget supplementation on nutrient intake, mid-upper arm circumference (MUAC), and body weight among pregnant women with Chronic Energy Deficiency (CED). Methods: A quasi-experimental study with a pretest-posttest control group design was conducted among 56 pregnant women with CED, who were assigned to either an intervention group or a control group (n=28 each). The intervention group received 200 g/day of Cornfish nuggets for 14 days. Nutrient intake, MUAC, and body weight were measured before and after the intervention and analyzed using a paired t-test and an independent t-test. Results: Cornfish nugget supplementation for 14 days significantly increased nutrient intake (p<0.05). Improvements in MUAC and body weight were observed in the intervention group following the intervention. Weight gain was higher in the intervention group than in the control group (0.48 kg vs 0.21 kg; p<0.05), whereas the increase in MUAC did not differ significantly between groups (p>0.05). Conclusion: Cornfish nuggets were effective in improving nutrient intake and body weight among pregnant women with CED; however, they did not demonstrate a significant effect on increasing MUAC during the 14-day intervention period.